Recovery of Coastal Fauna after the 2011 Tsunami in Japan as Determined by Bimonthly Underwater Visual Censuses Conducted over Five Years - Masuda, Reiji; Hatakeyama, Makoto; Yokoyama, Katsuhide; Tanaka, Masaru (PloS one, 2016)
Massive tsunamis induce catastrophic disturbance in marine ecosystems, yet they can provide unique opportunities to observe the process of regeneration. Here, we report the recovery of fauna after the 2011 tsunami in northeast Japan based on underwater visual censuses performed every two months over five years. Both total fish abundance and species richness increased from the first to the second year after the tsunami followed by stabilization in the following years. Short-lived fish, such as the banded goby Pterogobius elapoides, were relatively abundant in the first two years, whereas long-lived species, such as the black rockfish Sebastes cheni, increased in the latter half of the survey period. Tropical fish species were recorded only in the second and third years after the tsunami. The body size of long-lived fish increased during the survey period resulting in a gradual increase of total fish biomass. The recovery of fish assemblages was slow at one site located in the inner bay, where the impact of the tsunami was the strongest. Apart from fish, blooms of the moon jellyfish Aurelia sp. occurred only in the first two years after the tsunami, whereas the abundances of sea cucumber Apostichopus japonicus and abalone Haliotis discus hannai increased after the second year. Although we lack quantitative data prior to the tsunami, we conclude that it takes approximately three years for coastal reef fish assemblages to recover from a heavy disturbance such as a tsunami and that the recovery is dependent on species-specific life span and habitat.